Influence of animal glue on mineralogy, strength and weathering resistance of lime plasters. (30th November 2019) - Elert, Kerstin; García Sánchez, Rosa Maria; Benavides-Reyes, Cristina; Linares Ordóñez, Fátima
Highlights: Animal glue increases weathering resistance of lime-based materials. Animal glue reduces crack formation upon drying of plasters and improves adherence. Formation of an organic/inorganic hybrid material in the presence of animal glue. Abstract: In order to optimize lime plasters for conservation purposes, the influence of animal glue on the mineralogical evolution, mechanical properties, and weathering resistance was studied. The organic additive caused a decrease in carbonation rate and affected mechanical properties negatively, facilitating the formation of large air bubbles in the plaster matrix. However, the weathering resistance (water spraying/SO2 exposure) improved significantly. The organic additive also reduced crack formation and formed a physical barrier around the calcite crystals, which delayed sulfation. Lime-based composite materials are a valuable alternative to conventional lime plasters, showing improved adherence to the substrate and no significant color changes.